The North American Indian, vol. 3 supplement : The Teton Sious. The Yanktonai. The Assiniboin, 1908 - Curtis, Edward S., 1868-1952; Curtis, Edward S., 1868-1952 (University of Southern California Digital Library (USC.DL), 2016)
36 plates supplementing volume three of The North American Indian.